Ketoacidosis with euglycemia in a patient with type 2 diabetes mellitus taking dapagliflozin: A case report. Issue 3 (January 2019) - Yeo, Sang Mok; Park, Hayeon; Paek, Jin Hyuk; Park, Woo Yeong; Han, Seungyeup; Park, Sung Bae; Jin, Kyubok
Abstract: Rationale: Dapagliflozin (a sodium-glucose cotransporter-2 [SGLT2] inhibitor) represents the most recently approved class of oral medications for the treatment of type 2 diabetes. Dapagliflozin lowers plasma glucose concentration by inhibiting the renal reuptake of glucose in the proximal renal tubules. In 2015, the US Food and Drug Administration released a warning concerning a potential increased risk of ketoacidosis in patients taking this medication. Patient concerns: We present the case of a 23-year-old woman with type 2 diabetes treated with dapagliflozin (10 mg, once a day) for 2 years who presented to the emergency department with abdominal pain. Diagnoses: We diagnosed her with severe ketoacidosis with a normal glucose level (177 mg/dL) due to dapagliflozin, accompanying acute pancreatitis due to hypertriglyceridemia. We concluded that the precipitating factor for euglycemic ketoacidosis was pseudomembranous colitis. Interventions: She was treated with intravenous infusions of insulin, isotonic saline, and sodium bicarbonate as diabetic ketoacidosis treatment. Outcomes: She was in shock with severe metabolic acidosis. After continuous renal replacement therapy, the uncontrolled metabolic ketoacidosis was treated, and she is currently under follow-up while receiving metformin (500 mg, once a day) and short- and long-acting insulins (8 units 3 times and 20 units once a day). Lessons: We report an unusual case of SGLT2 inhibitor-induced euglycemic ketoacidosis recovered by continuous renal replacement therapy in a patient with type 2 diabetes and recurrent acute pancreatitis due to hypertriglyceridemia. We diagnosed a rare complication of the SGLT2 inhibitor in a patient with type 2 diabetes in whom uncontrolled metabolic ketoacidosis could be effectively managed via continuous renal replacement therapy.